Russia and "hybrid warfare" - Renz, Bettina (Taylor and Francis, 2016)
In the aftermath of the Crimea annexation in March 2014, the idea of ‘hybrid warfare’ quickly gained prominence as a concept that could help to explain the success of Russian military operations in this conflict. Although the concept continues to enjoy widespread popularity in both scholarly and policy circles, its utility as an analytical tool is also heavily contested. This article adds to the literature critical of the ‘hybrid warfare’ concept. It argues that in addition to the fact that what is now described as a ‘hybrid’ approach to war is in fact nothing new, the problems pertaining to its utility for the study of contemporary Russia go deeper than this. ‘Hybrid warfare’ inadequately reflects the direction of Russian military modernisation and as such has led to a skewed understanding of Russian military capabilities. Moreover, the tendency to use ‘hybrid warfare’ not only to conceptualise developments in the Russian military, but in the country’s foreign policy in general, can lead to serious unintended consequences.